A retrospective study on perineal lacerations in vaginal delivery and the individual performance of experienced mifwives. Issue 1 (December 2015) - Ott, Johannes; Gritsch, Evelyn; Pils, Sophie; Kratschmar, Sophie; Promberger, Regina; Seemann, Rudolf; Fürst, Sabine; Bancher-Todesca, Dagmar; Hauser-Auzinger, Christa
Abstract Background Medical staff's influence on patient outcomes has become a subject of interest. We evaluated experienced midwives and compared their performance concerning perineal lacerations (PL). Methods In a retrospective cohort study, 1937 women with singleton pregnancies who had delivered spontaneously with a cephalic presentation by experienced midwives in the Medical University of Vienna from January 2009 to April 2014 were included. As predictive parameters, we included basic patient-, pregnancy- and delivery-related characteristics including the individual midwife who delivered the child. The incidence of PL was the main outcome measure. Results Overall PL and severe PL were found in 508/1937 (26.2 %) and 19/1937 women (1.0 %), respectively. In a multivariate analysis for PL of any degree, maternal age (ß = 0.170 ± 0.080), gestational age at delivery (ß = 0.190 ± 0.320), and birth weight (ß = 0.002 ± 0.000) significantly increased the risk, whereas multiparity (ß = −0.379 ± 0.141) and mediolateral episiotomy (ß = −1.514 ± 0.284) decreased it (p  < 0.05). In addition, the individual midwife who delivered the child was a significant influencing factor, with ß-values ranging from −0.028 to 0.899 compared to the reference midwife. For severe PL, the midwife was not of significant influence. Conclusions The individual midwife is an independent factor that influences the risk for overall PL, not for severe PL. Other risk factors include maternal age, gestational age at delivery, birth weight, parity and episiotomy.